Health Risks Related to Impression Procedures in Dentistry - Z. Zdráhal; L. Vavřičková; R. Slezák (Czech Dental Chamber, 2010)
There is a lot of risks of methods used for impressions, which could be bent out or minimized. They are divided in risks evocated by impression materials and risks related to impression procedures. Hypersensitivity and toxic reactions belong to risks evocated by impression materials. More extensive are risks related to impression technique. They include damage of periodontal tissue, dismantling of the crown or bridge, holding retraction cord in the gingival sulcus, impression material as a foreign body in the maxillary sinus, vomiting, and the activation of HSV infection and aspiration of the impression material.